2019
DOI: 10.1155/2019/4039792
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Clinical Predictors of Poor Metabolic Control in Children with Type 1 Diabetes in Jordan

Abstract: Background. Achieving adequate metabolic control in children with type 1 diabetes is important in slowing the progression of future microvascular and macrovascular complications, but still it is a universal challenge. We aim to investigate possible factors associated with poor metabolic outcomes in Jordan as an example of a country with limited resources. Methods. This is a retrospective chart review study of children with type 1 diabetes. Several clinical and personal characteristics were tested for associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 38 publications
4
20
1
Order By: Relevance
“…In regard to predictors, the age of the participant was found to be signi cantly associated variables that determine time to rst optimal glycemic control. The study showed that, the time needed to reach rst optimal glycemic control is longer among clients of age group >10-14 years followed by the age group 6-10 years compared to clients in the age group<=5 years(AHR=0.324,95%CI=0.192-0.546), indicating that for children older than 10 years, the rate of achieving optimal glycemic control decreases as age increases which is in line with study done in Tanzania ,Bulgaria, Iraq, Taiwan and Jordan (26,46,47,49,50). This can be due to the fact that As a child develops, he/she under goes a varieties of physical and life style changes (24).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In regard to predictors, the age of the participant was found to be signi cantly associated variables that determine time to rst optimal glycemic control. The study showed that, the time needed to reach rst optimal glycemic control is longer among clients of age group >10-14 years followed by the age group 6-10 years compared to clients in the age group<=5 years(AHR=0.324,95%CI=0.192-0.546), indicating that for children older than 10 years, the rate of achieving optimal glycemic control decreases as age increases which is in line with study done in Tanzania ,Bulgaria, Iraq, Taiwan and Jordan (26,46,47,49,50). This can be due to the fact that As a child develops, he/she under goes a varieties of physical and life style changes (24).…”
Section: Discussionsupporting
confidence: 86%
“…Especially those clients whose care giver mother and father was two times more likely associated with rst optimal glycemic control as compared with clients supported by their mothers alone. The nding was supported by the study conducted in Tanzania and middle east Jordan (32,50).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…According to Baumer et al preplanned outpatient appointments were less likely to have been attended if a child did not live with both parents (78.8% vs. 83.7%, p < 0.001), indicating temporal constraints of single parents 35 . Other explanatory approaches may include difficulties in providing, supervising and monitoring diabetes management (i.e., regarding the SMBG frequency, meals and snacks) 20,36 ; a diabetes caregiver other than the mother 37 ; health literacy 38 ; prevalence of life stressors 36 ; and family dynamics, such as cohesion, support, and conflict 20,39 …”
Section: Discussionmentioning
confidence: 99%
“…This is because type 1 diabetes puts high demand on parents to learn multiple management skills, further on, basic levels of education is needed to know the importance of compliance and the consequences of poor control on long term complications, while knowing how to use more advanced technologies demands even higher skills, this finding is in coherence with other studies on the subject. 12,[19][20][21] Also within this context, a study involving 3 pediatric diabetic center in United Kingdom, showed that social deprivation, was associated with the least likelihood of initiation or success in intensive insulin therapy, a factor likely to contribute to poor diabetic control, this seemed to be mediated through lower educational levels. 22 In agreement with other studies, this study found that diabetic control was poorer in older pediatric age groups, this could partially be due to the surges in growth and sex hormones, and the psychological difficulties in adolescence causing less compliance and increased insulin resistance.…”
Section: Discussionmentioning
confidence: 99%